Legal Protections for Victims of Sexual Violence and the Rights of Victims - Silmi, Rhaniya; Hendriana, Rani; Budiyono, Budiyono; Barkhuizen, Jaco; Harahap, Salman Paris (Faculty of Law, Universitas Jenderal Soedirman, 2024)
WHO has conducted surveys from 2000 to 2018, revealing that out of 161 countries, at least one in three women in the world has experienced physical and/or sexual violence. Additionally, The United Nations Entity for Gender Equality and the Empowerment of Women states that an estimated 35% of women worldwide have experienced physical and sexual violence. The issues addressed in this research are the specific regulations on sexual violence criminal acts in Law Number 12 of 2022 concerning the Sexual Violence Crime Law and the legal protection policy for victims of sexual violence. This research adopts a normative juridical approach, utilizing a literature review as well as secondary data analysis with a statute approach. The research findings indicate that the specific regulations in Sexual Violence Crime Law can be classified based on their definitions, types, evidence arrangements, victim rights, and criminal sanctions. The victim rights encompass the right to assistance, restitution, and compensation, the right to temporary protection, the right not to appear at trial, and the rights related to handling, protection, recovery, and rights for the family of victims of sexual violence criminal. The new regulations and provisions in Sexual Violence Crime Law have introduced many new innovations, particularly in legal protection policies that are oriented towards the rights of victims. However, some aspects still need to be considered to ensure the effective implementation of these regulations. It is necessary to promptly establish further implementing regulations regarding granting victims' rights.